Determination of Stock Returns of Companies in the Various Industrial Sectors in 2022-2024 - Kadek Apriada; I Nyoman Kusuma Adnyana Mahaputra; Putu Riska Wulandari (Faculty of Economics and Business, Universitas Mahasaraswati Denpasar, 2026)
Purpose: This study aims to examine and obtain empirical evidence on whether profitability, liquidity, company size, price to book value, and leverage influence stock returns of companies in the Miscellaneous Industry Sector in 2022–2024. The population in this study is 65 companies in the miscellaneous industry sector listed on the Indonesia Stock Exchange in 2022–2024. Sampling used a purposive sampling technique, resulting in 40 companies with 3 years of observation, resulting in 120 research samples. Method: Data were analyzed using multiple linear regression analysis. Findings: The results of this study indicate that profitability and price-to-book value positively influence stock returns in companies in the Miscellaneous Industry Sector listed on the IDX during the 2022-2024 period. Meanwhile, liquidity, company size, and leverage have no effect on stock returns in companies in the Miscellaneous Industry Sector listed on the IDX during the period 2022-2024. Implications: This research provides practical and theoretical implications: in the context of companies in the miscellaneous industry sector listed on the Indonesia Stock Exchange for the 2022–2024 period, investors should focus more attention on profitability indicators and the price-to-book ratio (P/BV) when making investment decisions, as both variables have been shown to positively influence stock returns. This suggests that a company's ability to generate profits and market perception of its value are key indicators in determining stock returns.